Риск и корпоративная деятельность: определение - Клочкова, Наталия Владимировна; Кольцова, Елена Александровна (Современная экономика: проблемы и решения, 2017)
Purpose: article is devoted to problem of risk and corporate activity and their definition. Discussion: the term risk management does not yield to simple definition. The terms risk and management offer some clues оn content, although without prior knowledge, few would accurately guess the subject matter from the title. Certainly risk management is more specific than the title would have us believe; only some risks will be managed under our subject umbrella. Results: we proved that the class of risks does have distinguishing characteristics that set it apart from other forms of corporate risk, although in trying to achieve precise definitions, researchers find many poorly fitting cases. Despite these difficulties in formalizing a definition for our subject matter, authors have captured its general flavour.